Effect of Leafy Nutrition Humic Acid and Gibberellic Acid on Growth and Productivity of Barley - Fadhil Alaywe Atiyah Al-Rubaiee (Nabatia, 2023)
Pots experiment was carried out during the 2018 – 2019 growing season to study the effect of humic acid (0, 3, and 6mg.L-1) and gibberellic acid (0,100 and 200 mg.L-1) leafy nutrition and their interaction with barley ( Hordeum vulgare L.) growth and yield. The experiment was conducted as a randomized complete block design (RCBD) with three replicates, The means were compared at 0.05 according to the Least Significant Differential Test (LSD). The result showed a significant increase in plant height ( cm ), shoot dry weight ( g ), root dry weight ( g ), flag leaf area ( cm2 ), spike length ( cm ), number of spikes per plant, number of spikelets per spike, 100 grains weight, grains yield ( g / pot ), and total chlorophyll content (SPAD ), with increased concentration of Humic acid and gibberellic acid, and their interaction compared to control plants. Humic acid at 3 mg. L-1 and gibberellic acid at 100 mg. L-1 was the highest rate for all testing parameters.